Satisfactory level of Hiperskin TR® transparent film dressings in post-operative patient: a primary hospital Indonesia experience at Tebet District general hospital - Rosadi, Bramastha; Lawanto, Terry; Paula, Astrid; Jupri (International Surgery Journal, 2023)
Background: Post operative wound always be a burden, especially in tropical countries. The needs of extra care, avoidance from water/liquid, and routine changing of the dressings were the main concerned of the patients. The invention of waterproof dressings could decrease the hustle of wound care and increasing the comfort of the patients. This study aims to present satisfactory experience using transparent film dressing for post operative cases in primary care hospital Indonesia Methods: A descriptive study, total population of clean post operative wound from September to November 2022. Hiperskin TR®, a transparent film dressing was applied after cleaning the remaining debris. A questionnaire based on Bluebell wound healing questionnaire® was given at day 1 and day 7, to measure the satisfactory level of patients, and wound healing process experience. Results: 54 participants qualified for this study, but 6 were drop out. All of them were grouped by gender, age, and satisfactory level. Mostly were female (58%), with age ranging from 15-68 years old. The overall satisfaction of wound healing was good (66%), they felt secured (83.33%) and more comfortable using transparent dressing (83.33%). 12 patients (25%) needed to be changed before day 7 by health workers due to detachment of the dressing related to excessive/vigorous activities. 8 patients felt discomfort, 6 (12.5%) complained reddish and 2 patients (4.16%) have significant exudate within 1 week of follow up. Conclusions: The use of transparent film dressing for clean post operative wound at tropical country could be recommended, as it may decrease the patient’s disability in doing their daily activity and increasing patient’s satisfactory level.